A formação continuada na perspectiva das coordenadoras pedagógicas de creches municipais de Fortaleza - Leite, Maria Ilnair Martins (2013)
The objective of this study was to analyze daycare educational coordinators’ opinions about the continuous training offered by the Municipal Education Department of Fortaleza (MED) between 2008 and 2012. This study is based upon theories by Giroux (1992, 1997), Nóvoa (1997), Oliveira-Formosinho (2001, 2002, 2011), Wallon (1981, 1989) and Zeichner (1993, 1997). The methodology consisted of eight interviews with daycare educational coordinators of the municipal educational system of Fortaleza, who also discussed their opinions about the professional life, continuous training and the role these professionals play as educators in daycare centers, and two interviews with MED educational technicians about the continuous training. Analyses have shown that, overall, the educational coordinators value the continuous training, but point out several flaws, especially where it pertains to training content (because they don’t participate in content decisions and because practical matters aren’t deeply discussed) and the trainers themselves (who are mostly based on theories and need more practical information). Most educational coordinators recognize that the role as continuous training professionals is important, but there is some tension between that need and the lack of specific training and experience in the area. It’s possible to conclude that the objectives of the daycare educational coordinators’ continuous training need to be revised, considering that they not only need to articulate, but also internalize and transform the knowledge in daycare routine; in order to do that, their points of view on important themes must be considered, and trainers need to have deeper knowledge and more experience in childhood education.